Pengaruh Konsep Diri dan Minat Belajar Terhadap Disiplin Belajar Serta Implikasinya Terhadap Hasil Belajar Siswa - Sihotang, Mey A.; Gumilar, Gugum; Nurdianti, Raden Roro Suci (Civiliza Publishing, Indonesia., 2023)
The problem in this study is the low average learning outcomes of students in economic subjects. The purpose of this study was to determine the effect of self-concept and interest in learning on learning discipline and its implications for learning outcomes. This study uses a quantitative survey-type research method with an explanatory survey design. The population in this study was all students of Class XI IPS SMA Negeri 7 Tasikmalaya in the 2022–2023 academic year, as many as 208 students. The sampling technique used is a saturated sample, so the entire population in this study is used as a research sample. Data collection techniques using observation and questionnaires or surveys and data analysis techniques using path analysis The results showed that 1) Self-concept has no effect on learning discipline as seen from the significance value of 0.255. 2) Interest in learning has a significant effect on learning discipline with a significance value of 0.000. 3) Self-concept has a significant effect on learning outcomes with a significance value of 0.000. 4) Interest in learning significantly affects learning outcomes with a significance value of 0.000. 5) Learning discipline affects learning outcomes with a significance value of 0.000. 6) Self-concept does not affect learning outcomes through learning discipline with a t count of 1.12 which is less than t table 1.97. 7) Interest in learning influences learning outcomes through learning discipline with a t count of 4.080 greater than t table 1.97.